2018
DOI: 10.3389/fpsyg.2018.01326
|View full text |Cite
|
Sign up to set email alerts
|

Do Patients With Depression Prefer Literal or Metaphorical Expressions for Internal States? Evidence From Sentence Completion and Elicited Production

Abstract: In everyday communication metaphoric expressions are frequently used to refer to abstract concepts, such as feelings or mental states. Patients with depression are said to prefer literal over figurative language, i.e. they may show a concreteness bias. Given that both emotional functioning and the processing of figurative language may be altered in this clinical population, our study aims at investigating whether and how these dysfunctions are reflected in the understanding and production of metaphorical expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 48 publications
0
17
0
1
Order By: Relevance
“…These last studies did not deal precisely with metaphor types for depression, but with the metaphorical capacity of people diagnosed with depression. In this sense, the recent study by Kauschke, Mueller, Kircher, and Nagels (2018) reveals that the understanding and production of metaphorical expressions is completely preserved in patients with depression, with no significant differences from the healthy control group.…”
Section: State Of the Art On Metaphors Of Depressionmentioning
confidence: 92%
“…These last studies did not deal precisely with metaphor types for depression, but with the metaphorical capacity of people diagnosed with depression. In this sense, the recent study by Kauschke, Mueller, Kircher, and Nagels (2018) reveals that the understanding and production of metaphorical expressions is completely preserved in patients with depression, with no significant differences from the healthy control group.…”
Section: State Of the Art On Metaphors Of Depressionmentioning
confidence: 92%
“…The basic claim here is that the competence in figurative language comprehension relies on inferencing skills and the ability to integrate information from various sources (Gibbs, 1992;MacKey & Shaw, 2006;Rundblad & Annaz, 2010). Other factors and mechanisms might also play a role in figurative language processing, such as the type of embodiment pattern activated (Barsalou, 2008;Bergen, 2012); the state of mind and inner states or mood (Charteris-Black, 2012;Kauschke et al, 2018), and probability and heuristic factors (Tversky & Kahneman, 1974;Ritchie, 2013;Hetmański, 2015). Holistic assessment of these factors is still a challenge, although it is obvious that the interplay of various factors and mechanisms can shed light on the process of inferencing.…”
Section: Tripartite Research Methodology In Figurative Responses Procmentioning
confidence: 99%
“…Moreover, when looking at metaphoric and figurative language, research has shown among MDD patients significant impairments in the production of metaphors, that is, a lesser tendency to verbalize positive contents [75], and a “concreteness bias” when providing verbal descriptions of a picture [77]. Nevertheless, if concretism has been widely observed in schizophrenia, it is currently unclear whether or not, and to what extent, metaphorical processing is affected in patients with depression [75].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, when looking at metaphoric and figurative language, research has shown among MDD patients significant impairments in the production of metaphors, that is, a lesser tendency to verbalize positive contents [75], and a “concreteness bias” when providing verbal descriptions of a picture [77]. Nevertheless, if concretism has been widely observed in schizophrenia, it is currently unclear whether or not, and to what extent, metaphorical processing is affected in patients with depression [75]. Indeed, some studies have highlighted the presence of difficulties among MDD patients in processing figurative language and in interpreting metaphors [71, 73, 74, 76], while other studies, comparing metaphorical interpretation among subjects with depression and controls, did not observe difficulties with metaphorical processing per se and emphasized strong interpretational negativism, that is, selection and overrepresentation of negative content [86].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation